Targeting c-Jun in A549 Cancer Cells Exhibits Antiangiogenic Activity In Vitro and In Vivo Through Exosome/miRNA-494-3p/PTEN Signal Pathway - Shao, Chen; Huang, Yingying; Fu, Bingjie; Pan, Shunli; Zhao, Xiaoxia; Zhang, Ning; Wang, Wei; Zhang, Zhe; Qiu, Yuling; Wang, Ran; Jin, Meihua; Kong, Dexin (Frontiers in Oncology, 2021)
The oncogene c-Jun is activated by Jun N-terminal kinase (JNK). Exosomes are nanometer-sized membrane vesicles released from a variety of cell types, and are essential for cell-to-cell communication. By using specific JNK inhibitor SP600125 or CRISPR/Cas9 to delete c-Jun, we found that exosomes from SP600125-treated A549 cancer cells (Exo-SP) or from c-Jun-KO-A549 cells (Exo-c-Jun-KO) dramatically inhibited tube formation of HUVECs. And the miR-494 levels in SP600125 treated or c-Jun-KO A549 cells, Exo-SP or Exo-c-Jun-KO, and HUVECs treated with Exo-SP or Exo-c-Jun-KO were significantly decreased. Meanwhile, Exo-SP and Exo-c-Jun-KO enhanced expression of phosphatase and tensin homolog deleted on chromosome ten (PTEN). Addition of miR-494 agomir in Exo-c-Jun-KO treated HUVECs inhibited PTEN expression and promoted tube formation, suggesting the target of miR-494 might be PTEN in HUVECs. Moreover, A549 tumor xenograft model and Matrigel plug assay demonstrated that Exo-c-Jun-KO attenuated tumor growth and angiogenesis through reducing miR-494. Taken together, inhibition of c-Jun in A549 cancer cells exhibited antiangiogenic activity in vitro and in vivo through exosome/miRNA-494-3p/PTEN signal pathway.